Contemporary Study of Ihtikar According to Scholars and the Effect of ihtikar practices in the Economy - Ahmad Maulidizen; Nur Atikah; Yuni Sahara (Jurnal Ilmiah Ekonomi Islam, 2019)
Ihtikar is a sale and purchase transaction which fulfills the terms and conditions in the sale and purchase contract, but is included in prohibited transactions. In practice, many people are still confused about the ihtikar problem. There are differences regarding the law and the object of Ihikar as transactions that are prohibited from social and economic interests. Therefore, this article will explain the ihtikar law according to scholars and the impact of its application on the economy. This article is a central study with qualitative assessment, a method of collecting data with documentation originating from journals, books and other sources, which are then analyzed by inductive, deductive and comparative methods. The results of the study found that the verses and hadith raised in this paper textually prohibit the existence of ihtikar. Ihtikar law is haram if the goods stockpiled are needed by the community which results in price increases. When this happens, Islam allows for intervention in these economic activities by issuing policies and rules that affect normal prices